The Association of ACTN3 Rs1815739 Polymorphism with Various Malocclusion Phenotype - (:unkn) unknown (My University, 2022)
Objective:A functional polymorphism on the 16th exon of the alpha-actinin-3 gene has an effect on the protein structure and cellular signaling and therefore on muscle contraction. In this study, we aimed to analyze the alpha-actinin-3 rs1815739 polymorphism in 3-dimensional malocclusions and different craniofacial skeletal patterns.Methods:Forty-nine volunteering subjects enrolled for the study. Genotyping of alpha-actinin-3 rs1815739 polymorphism was per- formed using real-time polymerase chain reaction. Pre-orthodontic cephalometric radiographs were traced using NemoTech ceph- alometric tracing software. IBM SPSS Statistics for Windows was utilized to carry out statistical analysis.P<.05 was considered to be statistically significant.Results:The respective numbers and the percentages of alpha-actinin-3 rs1815739 polymorphisms for RR, RX, and XX genotypes were 39 (79.6%), 4 (8.2%), and 6 (12.2%), respectively. Twenty-one patients had low angle vertical patterns and 17 patients had Class I and the same number of the patients had Class III facial patterns. But none of these had statistically significant difference in terms of alpha-actinin-3 rs1815739 polymorphism and in vertical or sagittal facial patterns, and mandibular incisor inclination. When we examined the maxillary anteroposterior position, we found a significant difference between rs1815739 polymorphisms (P<.05). Also, we detected a significant difference between rs1815739 polymorphism and maxillary incisor inclination (P<.05).Conclusion:Maxillary incisor inclination and maxillary anteroposterior position are associated with alpha-actinin-3 rs1815739 poly- morphism in a Turkish cohort.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); ACTN3; facial pattern; malocclusion; polymorphism; MUSCLE-FIBER-TYPE; GENE; GROWTH; R577X; ALPHA-ACTININ-3